2008
DOI: 10.1097/01.njh.0000319178.32918.6b
|View full text |Cite
|
Sign up to set email alerts
|

Supporting a Community of Individuals With Intellectual and Developmental Disabilities in Grieving

Abstract: Individuals with intellectual and developmental disabilities are living longer and experiencing deaths among their family and peers, yet their grieving is not well recognized. Staff members who provide care for these individuals witness the aging and death of their clients, yet they also receive little preparation to work through issues surrounding bereavement for their clients and themselves. The End of Life Nursing Education Consortium developed a national initiative to improve end-of-life and bereavement ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Clients participated in the development of the program for the Day of Remembrance, including in the song selection and reading poetry. Clients and staff expressed that the activity opened up dialogue about their needs concerning grief and loss, and the agency continues with regular educational programs for staff on how to support clients and themselves in these areas (Adamji et al, 2004;Ailey, O'Rourke, Breakwell, & Murphy, 2008).…”
Section: Supporting Individuals With I/dd and Their Staff In Grief Anmentioning
confidence: 99%
“…Clients participated in the development of the program for the Day of Remembrance, including in the song selection and reading poetry. Clients and staff expressed that the activity opened up dialogue about their needs concerning grief and loss, and the agency continues with regular educational programs for staff on how to support clients and themselves in these areas (Adamji et al, 2004;Ailey, O'Rourke, Breakwell, & Murphy, 2008).…”
Section: Supporting Individuals With I/dd and Their Staff In Grief Anmentioning
confidence: 99%
“…Despite their problems, group homes can provide supportive environments and contribute to the quality and security of life, including developing social climates that promote less social distance between residential staff and residents and that promote the social networks of residents with intellectual disabilities (Robertson et al, 2001). Residential staff members provide assistance with residents' many needs and report their relationships as a source of satisfaction; some view their jobs as a calling (Ailey, O'Rourke, Breakwell, & Murphy, 2008). The findings of a study conducted in large residential centers among individuals with mild and moderate intellectual disabilities showed that group decision‐making about common problems facing the group of residents improved the decision‐making of the individuals in the group (Heller, 1978).…”
Section: Introductionmentioning
confidence: 99%